The Impact of Emotional Labor and Workplace Incivility on Psychological Well-Being in Restaurants in Denpasar City with Burnout as a Mediating Variable - WIBAWA, I Made Aryan Satriya; PUTRA, Ida Bagus Udayana; INDIANI, Ni Luh Putu (PT Keberlanjutan Strategis Indonesia, 2025)
The restaurant industry in Denpasar, Bali, is growing rapidly due to high tourism demand, leading to intense competition and pressure on employees. This study examines the impact of emotional labor and workplace incivility on psychological well-being, with burnout as a mediating variable. Data were collected from 180 restaurant employees in Denpasar through questionnaires and analyzed using Partial Least Squares (PLS).The study found that emotional labor had a positive effect on psychological well-being (β=0.226, p=0.005), supported by the internalization of Balinese cultural values ​​such as Tri Hita Karana and pride in working in the tourism sector, which transform emotional demands into a source of satisfaction. Meanwhile, workplace incivility also showed a positive effect on psychological well-being (β=0.871, p<0.001), indicating that employees develop resilience and utilize social support to transform incivility into a challenge that fosters personal growth. However, workplace incivility significantly increased burnout (β=1.061, p<0.001), indicating that even though incivility was initially perceived as a challenge, it still drained psychological resources. Emotional labor did not directly lead to burnout (β=-0.128, p=0.056), nor did burnout significantly affect psychological well-being (β=-0.171, p=0.081), likely due to cultural and spiritual support in Bali. However, burnout significantly mediated the effects of emotional labor (β=0.282, p=0.028) and workplace incivility (β=-0.387, p=0.001) on psychological well-being, underscoring the role of cultural coping in workplace psychological dynamics.